E-Commerce Disputes and the Law of Default: Is the Indonesian Civil Code Still Adequate? - Ibrahim, Nanang; Fenanlabir, Marsel (Jurnal Ilmu Hukum Kyadiren, 2025)
The rapid growth of e-commerce in Indonesia has introduced new challenges in applying the concept of default (breach of contract) as outlined in the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata/KUHPerdata), which has not yet fully accommodated the unique characteristics of digital transactions. This study aims to reconstruct the legal concept of default to better align with the nature of electronic contracts, identify various forms of breach occurring within the e-commerce ecosystem, and propose a dispute resolution framework grounded in civil law principles, consumer protection, and digital innovation. Employing a normative juridical approach and comparative legal analysis, this research finds that defaults in e-commerce transactions are often transnational and multifaceted, involving business actors, consumers, and digital platforms, while encompassing new issues such as data security breaches and technological system failures. The study recommends regulatory reform through the development of a national Online Dispute Resolution (ODR) model and the harmonization of relevant sectoral laws. In conclusion, adapting the traditional concept of default and promoting innovation in dispute resolution mechanisms are essential to ensure legal certainty and fairness in the digital era.